Crescimento vegetativo e análises químicas do óleo essencial de Chenopodium ambrosioides L. sob três fontes de adubos orgânicos - Bibiano, Camila Silva (2015)
Chenopodium ambrosioides L., known as santa maria herb, mastruz herb or epazote, is a medicinal plant belonging to the Amaranthaceae family, widely used in the popular medicine in all the world; essentially in the treatment of worm and cutaneous wounds. However, studies about its management, cultivation and nutrition are incipient so far. In this study, we aimed to verify the effect of different doses of organic fertilizers in the production of vegetal biomass, yield, and content and quality of essential oil of C. ambrosioides. The experiment was performed in a greenhouse for 60 days, in completely randomized design with 5 replications. Treatments were arranged in 3×5+1 factorial scheme, i.e., three sources of fertilizer and 5 doses per fertilizer. Each parcel consisted of 4 plants. Doses of bovine manure, chicken, and quail influenced significantly the production of plants biomass, as well as the content, yield, and chemical composition of essential oil of santa maria herb. The dose of chicken manure about 15.08 kg.m2 contributed to the obtaining of the greatest content of dry biomass, about 17.97g. The quail manure showed greater efficiency in the production of total dry biomass, with 14.48g obtained for the dose about 8.93 kg.m2. The greatest content of essential oil was obtained from inflorescences, followed by that obtained from leaves. There was no essential oil from stem and other plant parts. The greatest content of essential oil, obtained by means of hydrodistillation of inflorescences, ranged from 0.59 to 1.85%; and the bovine manure was found to be the most efficient for this parameter. Eight chemical compounds from the essential oil of C. ambrosioides were found. The ascaridole, α-terpinene, p-cymene and isoascaridole were influenced with the increase of doses of fertilizers, specially the increase of bovine and quail manures. The content of ascaridole decreased and the content of p-cymene increased when 9 kg/m2 and 12 kg/m2 of manure were applied.